Human Resource Management (HRM) in BAZNAS’s Rice ATM Program in Depok Municipality - Laeli, Azah Nur; Zen, Muhamad (Munazzama: Journal of Islamic Management and Pilgrimage, 2024)
Human resource management plays an important role in how successful an organization or company can be. Human resource management is of utmost importance since it determines whether or not organizational goals can be achieved. One of such organizations with goals to achieve is BAZNAS of Depok Municipality with its Rice ATM program. It is a program to distribute rice that requires human resources to play some role in its implementation. Therefore, the existing human resources must be managed well to achieve its objectives. This research is qualitative with a descriptive approach. Such research attempts to interpret and describe the existing data. This research aims to find out the implementation, procedures and human resource management (HRDM) in BAZNAS’s Rice ATM program in Depok Municipality. The data were collected using observation, interviews, and documentation. This research found that human resources were managed fairly well in the Rice ATM program in procurement and planning. This was shown by the fact that Depok Municipality BAZNAS could cooperate and collaborate with the Zakat Collection Units (UPZ). However, the program’s maintenance and evaluation were still weak. On how it was implemented, BAZNAS would provide the rice ATMs and the program would be run by UPZs. Thanks to this mechanism, the rice assistance could be distributed more quickly to the community, making it easier to achieve the goal.